Quality of Online Learning Services in Graphic Design And Publishing Courses During The Covid-19 Pandemic - Bagus Yunianto Wibowo; Mellasanti Ayuwardani (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
The Covid-19 pandemic that has hit the entire world has caused all activities to be carried out online (online) including learning activities. Experience is lacking and is something that is still unfamiliar in Indonesia in conducting online learning,  causing several obstacles and difficulties in delivering learning optimally, especially in practical courses.  The problem of this research is "How is the Quality of Online Learning Services  in Graphic Design and Publishing Courses  during the Covid-19 Pandemic". The purpose of this research is the development of a conceptual integration model in the quality of online learning services  expected by students. The sample size of this study was 21 respondents. The method of data collection is done by providing a list of questions using Google Form.  Reliability results are considered good enough; Responsiveness, Assurance and Attention are considered good; Direct Evidence (Tangible) has not been good.  The conclusion in this study was obtained to conclude that the limited facilities and infrastructure and costs owned by students in conducting practical lectures   online during the COVID-19 pandemic caused many obstacles in carrying out a quality online service process.